Review of Online Evidence-based Practice Point-of-Care Information Summary Providers: Authors' Reply to the Response by the Publisher of DynaMed - Banzi, Rita; Liberati, Alessandro; Moschetti, Ivan; Tagliabue, Ludovica; Moja, Lorenzo (JMIR Publications, 2010)
We are pleased that the publisher of DynaMed clarified his evidence-based methodology in response to our review. We stress again how good reporting is a prerequisite for transparency. This lesson comes from the reporting of research findings but its extension to the development of information sources should be considered.